The Influence of Work-Life Balance and Work Culture on Generation Z Turnover In Semarang City - Umi Nurul Khasanah; Muhammad Nur Abdi (Cita konsultindo, 2026)
This study aims to analyze the effect of work-life balance and work culture on turnover intention among Generation Z employees in Semarang City, as well as to identify the most dominant variables influencing their decision to leave the organization. This study uses a quantitative approach with a survey method. The research population consists of Generation Z employees (born between 1997 and 2012) working in various industrial sectors in Semarang City. The sample will be selected using purposive sampling with a sample size of 150 people. Data collection will be conducted through a structured questionnaire that has been tested for validity and reliability. Data analysis techniques use multiple linear regression or Structural Equation Modeling (SEM) to test the relationship between variables and identify direct and indirect effects. The results of the study show that work-life balance has a negative and significant effect on the turnover intention of Generation Z human resources in Semarang City (t-statistic = -2.398, p-value = 0.000 < 0.05). In addition, there is a positive and significant impact of Work Culture on the Turnover Intention of Generation Z Human Resources in Semarang City (statistical t = 0.249, p value = 0.000 > 0.05).